In Search of Structured Business Model for Renewable Energy Expansion in India - Phukon, Abhijit; Gakhar, Divya Verma (International Research Journal of Management, IT & Social Sciences, 2016)
While overall power generation in India has been increasing over the years, the coverage of households in the energy access net (with 38% of total households or over 500 million people having no energy access) and availability of supply (at only 5-6 hours/day) are still prime concerns for the Government.Â  In such a scenario, is renewable energy an alternative given the shortage of supply from conventional sources, with over 30,000 MW stranded power plants, commitment of the Government to set up 100 Smart Cities, High-speed/Semi-speed Rails, Industrial Corridors and more beyond that âpower to allâ by 2022â Through this study, an attempt has been made to understand the socio-economic-environmental impact of renewable energy expansion and examined the factors that govern the feasibility and/or viability in meeting the ambitious clean energy target of 175 GW set out by the Government. The key determinants of renewable energy are found to be functionality variation, pattern of householdâs energy consumption, willingness-to-pay, behavioral change in tariff and cost, grid integration, energy efficiency and access to cheap green finance. Selective implementation of a combination of On-Grid, Off-Grid and localized Mini-Grids application and flexible revenue modality such as âPay as-you-goâ in off-grid areas and âNet-meteringâ or âFeed-in-tariffâ concept in grid-connected areas are best suited. Further, enforceable renewable purchase obligation, renewable generation obligation, faster and efficient implementation of renewable energy certificates as tradable commodity, carbon trading as a source of revenue, green marketing, mobilization of funds under corporate social responsibility and single procurement of all renewable energy by a centralized unit would go a long way in achieving the renewable targets.